2008
DOI: 10.1021/ja710484d
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Fiber Formation and Membrane Disruption are Separate Processes Localized in Two Distinct Regions of IAPP, the Type-2-Diabetes-Related Peptide

Abstract: Aggregation of Islet Amyloid Polypeptide (IAPP) has been implicated in the development of type II diabetes. Because IAPP is a highly amyloidogenic peptide, it has been suggested that the formation of IAPP amyloid fibers causes disruption of the cellular membrane and is responsible for the death of β-cells during type II diabetes. Previous studies have shown that the N-terminal 1-19 region, rather than the amyloidogenic 20-29 region, is primarily responsible for the interaction of the IAPP peptide with membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
260
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(291 citation statements)
references
References 35 publications
25
260
0
1
Order By: Relevance
“…The importance of postion-18 is consistent with NMR studies of IAPP fragments in the presence of model membranes (45). hIAPP [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] and rIAPP [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] , which differ only in the identity of residue-18, bind membranes in different orientations, and these differences are believed to correlate with the difference in the potential for membrane disruption (45,46). In summary, our data dissociate IAPP-induced leakage of standard model membranes from direct cellular toxicity, thereby indicating that further studies to identify the precise mechanism (s) of IAPP cellular toxicity are essential for the optimal development of therapeutic strategies to prevent T2D and islet graft failure.…”
Section: Discussionsupporting
confidence: 56%
“…The importance of postion-18 is consistent with NMR studies of IAPP fragments in the presence of model membranes (45). hIAPP [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] and rIAPP [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] , which differ only in the identity of residue-18, bind membranes in different orientations, and these differences are believed to correlate with the difference in the potential for membrane disruption (45,46). In summary, our data dissociate IAPP-induced leakage of standard model membranes from direct cellular toxicity, thereby indicating that further studies to identify the precise mechanism (s) of IAPP cellular toxicity are essential for the optimal development of therapeutic strategies to prevent T2D and islet graft failure.…”
Section: Discussionsupporting
confidence: 56%
“…Our present work supports p3 and N9 channel-mediated toxicity and suggests that ion channel blocking strategies for these smaller amyloid fragments may present an important therapeutic avenue for treatments for sporadic AD and Down syndrome. Our work has far broader relevance beyond the boundaries of amyloid-related neurodegenerative diseases (43). The discovery that nonamyloidogenic peptides may be pathogenic when oligomerized and embedded in membranes is startling and may require a reevaluation of the pathophysiology of these diseases.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, it was reported that the amino acid sequences responsible for amyloid formation and membrane disruption are located in different regions of the peptide and amyloid formation can occur independently from membrane disruption [29,30]. The C-terminal domain has amyloidogenic property, and the N-terminal fragment of hIAPP was alone sufficient to induce membrane perturbation and a single mutation abolished the activity [31][32][33].…”
Section: Resultsmentioning
confidence: 99%